2005
DOI: 10.1111/j.1365-2958.2005.04810.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of CcpN in the regulation of a novel untranslated RNA (SR1) in Bacillus subtilis

Abstract: SummaryAntisense-RNAs have been investigated in detail over the past 20 years as the principal regulators in accessory DNA elements such as plasmids, phages and transposons. However, only a few examples of chromosomally encoded bacterial antisense RNAs were known. Meanwhile, ª ª ª ª 70 small non-coding RNAs from the Escherichia coli genome have been found, the functions of the majority of which remain to be elucidated. Only one systematic search has been performed for Gram-positive bacteria, so far. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
177
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(179 citation statements)
references
References 42 publications
1
177
1
Order By: Relevance
“…The presence of potential binding sites for other protein factors can also give clues to the regulatory process controlled by a particular RNA. For instance, for B. subtilis, this was reported for the Fur-dependent FsrA sRNA, which regulates the iron-sparing response (43), and the gluconeogenesis sRNA SR1, which is regulated by CcpA and CcpN (44).…”
Section: Clues For Predicting Regulatory Rna Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of potential binding sites for other protein factors can also give clues to the regulatory process controlled by a particular RNA. For instance, for B. subtilis, this was reported for the Fur-dependent FsrA sRNA, which regulates the iron-sparing response (43), and the gluconeogenesis sRNA SR1, which is regulated by CcpA and CcpN (44).…”
Section: Clues For Predicting Regulatory Rna Functionsmentioning
confidence: 99%
“…Instead, there are seven regions of complementarity between the coding part of ahrC and the 3= end of SR1. SR1 has been reported to be exclusively expressed under gluconeogenic conditions, because of its repression by CcpN and CcpA (44). SR1 was later found to encode a 39-amino-acid peptide that increases mRNA stability of the gapA operon by binding to the GapA protein via an unknown mechanism.…”
Section: Independently Expressed Small Rnas and Rna Antitoxinsmentioning
confidence: 99%
“…127) B. subtilis possesses NADH-and NADPH-dependent glyceraldehyde-3-P dehydrogenases, which are specific for glycolysis and gluconeogenesis and are encoded by gapA and gapB respectively. 131) This protein also represses sr1, 132) which encodes a small non-coding regulatory RNA that inhibits the translation of ahrC encoding a transcriptional regulator that activates the rocABC and rocDEF operons for arginine catabolism and represses the gene cluster for arginine biosynthesis. 108,[133][134][135] CcpN is active when cells are growing on a glycolytic substrate, even if the medium also contains a gluconeogenic substrate.…”
Section: Catabolite Control Mediated By Ccpb Ccpc Ccpn and Cggrmentioning
confidence: 99%
“…Recently, we have demonstrated that SR1, which was found by using a computational approach and subsequent Northern blotting (24), acts by base pairing with its primary target, ahrC mRNA encoding the transcriptional activator of the rocABC and rocDEF arginine catabolic operons (17). Seven complementary regions between SR1 and ahrC were identified, and the most 5Ј region, region G, is located 97 nucleotides (nt) downstream from the ahrC ribosome binding site.…”
mentioning
confidence: 99%
“…In Bacillus subtilis, 24 sRNAs are known (1,24,35,39,40), and targets for 5 of them have been identified; RatA controls the toxin TxpA (39), SR1 controls the transcription activator AhrC (17) (see below), FsrA regulates sdhCAB, citB, yvfW, and leuCD (11), and BsrA and BsrB are two 6S RNAs (1). In Staphylococcus aureus, in addition to RNAIII (3), 12 novel sRNAs from pathogenicity islands have been detected (33).…”
mentioning
confidence: 99%